Evolution of Brain Magnetic Resonance Imaging Lesions in Dogs Treated for Meningoencephalomyelitis of Unknown Origin Between Initial Diagnosis and Relapse - Carole Soulé; Laurent Blond; Robin Cavalerie; Stéphanie Piazza; Clément Baudin‐Tréhiou (Journal of Veterinary Internal Medicine)
ABSTRACT Background The response of meningoencephalitis of unknown origin (MUO) in dogs to immunosuppressive treatment is unpredictable, and relapses frequently occur. Objectives Our aim was to describe the evolution of brain magnetic resonance imaging (MRI) lesions in dogs treated for MUO from diagnosis to relapse and to define the diagnostic and clinical value of repeat MRI at relapse. Animals Eighteen dogs treated for MUO that experienced relapse and underwent MRI both at disease onset and relapse. Methods Retrospective, descriptive, longitudinal, case series study. Dogs were identified from medical records between 2015 and 2024. The MR images were reviewed by radiologists for lesion number, location, size, pre‐ and post‐contrast signal aspect, meningeal enhancement, mass effect, perilesional edema, and evidence of intracranial hypertension. Results Median interval between MRIs was 259 days (range, 31–876 days). In dogs with relapse delay < 157 days, lesion number tended to decrease. Residual lesions tended to enlarge and exhibit contrast enhancement and perilesional edema (suggesting an active pathologic process), but without development of new lesions. After 233 days, all dogs had developed new lesions. Half exhibited enlarged active residual lesions, whereas the others showed either remission or smaller inactive lesions. Conclusions Before a clinical relapse at approximately 6 months, remission of the initial pathologic process and development of new lesions appear unlikely. Beyond this period, new lesions may occur with or without remission of the initial pathologic process, and repeat MRI is of high diagnostic and clinical value in detecting new lesions and characterizing the underlying pathologic process.